2020
DOI: 10.1002/hed.26363
|View full text |Cite
|
Sign up to set email alerts
|

Minimally important differences for interpreting European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 scores in patients with head and neck cancer

Abstract: Background: We aimed to estimate minimally important difference (MID) for interpreting group-level change over time for European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire core 30 (EORTC QLQ-C30) scores in head and neck cancer. Methods: Data were derived retrospectively from two published EORTC trials. Clinical anchors were selected using correlation strength and clinical plausibility of the given anchor/QLQ-C30 scale pair. MIDs for within-group and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 29 publications
4
46
0
Order By: Relevance
“…anchor scores indicating a low health status were associated with lower HRQOL scores). This compares well to MIDs already developed in this EORTC project for head and neck cancer [ 22 ], advanced breast cancer [ 21 ], malignant melanoma [ 20 ], colorectal [ 23 ] and ovarian [ 24 ] as well as to other similar research [ 26 28 ]. With two exceptions (global quality of life, diarrhoea), these MIDs were larger for deterioration compared to improvements.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…anchor scores indicating a low health status were associated with lower HRQOL scores). This compares well to MIDs already developed in this EORTC project for head and neck cancer [ 22 ], advanced breast cancer [ 21 ], malignant melanoma [ 20 ], colorectal [ 23 ] and ovarian [ 24 ] as well as to other similar research [ 26 28 ]. With two exceptions (global quality of life, diarrhoea), these MIDs were larger for deterioration compared to improvements.…”
Section: Discussionsupporting
confidence: 80%
“…This aligns with existing findings even beyond the QLQ-C30 [ 17 , 20 , 21 ], suggesting that patients may have a higher sensitivity to favourable differences [ 26 , 29 , 30 ]. However this effect is not universal as other studies have reported no systematic differences in the magnitude of change between deteriorating and improving scores [ 15 , 19 , 22 ].…”
Section: Discussionmentioning
confidence: 73%
“…Generally, MIDs for most scales were within the range of 4-10 points, which is similar to the 5-10 point range reported by Osoba et al [3] in breast and small-cell lung cancer. A similar range was also observed by Cocks et al [4] in pooled data across multiple cancer sites, by Musoro et al [6,12,14,15] in malignant melanoma, advanced breast cancer and head and neck cancer respectively, and by Maringwa et al [7,8] in lung and brain cancer respectively. We observed that MIDs for deterioration were lower than those for improvement, except for the diarrhoea scale.…”
Section: Discussionsupporting
confidence: 80%
“…This rule mainly stems from overlaps in initial guidelines by King [2] and Osoba et al [3] for interpreting the EORTC QLQ-C30. However, there is increasing evidence that MIDs can vary by EORTC QLQ-C30 scales, direction of change (improvement/deterioration) and clinical settings [4,6,7,12,14]. This implies that a global rule for MIDs applicable to all settings is highly unlikely [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation